2021
DOI: 10.3390/insects12040360
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Santolina chamaecyparissus and Tagetes patula Essential Oils on Biochemical Markers of Oxidative Stress in Aphids

Abstract: This study investigated the toxicity of essential oils (EOs) from Santolina chamaecyparissus (L.) and Tagetes patula (L.) towards the green peach aphid Myzus persicae (Sulzer) and the bird cherry-oat aphid Rhopalosiphum padi (L.). The effects of the EOs on aphid population parameters and levels of biochemical markers of oxidative stress within insect tissues were analyzed. In laboratory bioassays, application of the studied EOs at sublethal concentrations reduced daily fecundity and led to a decrease in the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 56 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…One of the mechanisms of insecticides is thought to be their ability to cause oxidative stress in insects ( Akbar et al, 2012 ; Lazarevic et al, 2020 ; Czerniewicz and Chrzanowski, 2021 ). In our study, we found significant enrichment of superoxide dismutase activity (GO: 0004784), response to oxidative stress (GO: 0006979), oxidation-reduction process (GO: 0055114) and response to ethanol (GO: 0045471) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…One of the mechanisms of insecticides is thought to be their ability to cause oxidative stress in insects ( Akbar et al, 2012 ; Lazarevic et al, 2020 ; Czerniewicz and Chrzanowski, 2021 ). In our study, we found significant enrichment of superoxide dismutase activity (GO: 0004784), response to oxidative stress (GO: 0006979), oxidation-reduction process (GO: 0055114) and response to ethanol (GO: 0045471) pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about ROS generation in aphids. However, the presence of these molecules has been found in the tissues of cereal aphids [ 56 , 57 , 58 , 59 ], the pea aphid Acyrtosiphon pisum (Harris) [ 60 , 61 ] and the green peach aphid Myzus persicae (Sulzer) [ 62 ]. Our data demonstrate clear differences in ROS content between various morphs of A. fabae occurring on the primary host.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our earlier studies showed that the exposure of cereal aphids to o-dihydroxyphenols caused the accumulation of H 2 O 2 and lipid peroxidation products in their tissues [ 58 ]. Moreover, treatment with essential oils induced ROS generation and damage to lipids within the tissues of M. persicae and R. padi [ 62 ]. The host plants and their specific chemical compositions can affect the oxidative balance of aphids.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous research has shown that several EOs from Asteraceae plants have toxic properties against aphids R. padi and M. persicae. The oils reduced the aphids' biological parameters and significantly inhibited the activity of AChE and Na + /K + -ATPase, the key enzymes of the insect nervous system [19,20]. However, an important aspect of the insecticidal activity of EOs is also their effect on aphid settling and feeding behavior.…”
Section: Introductionmentioning
confidence: 99%